2016
DOI: 10.5301/ejo.5000911
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Choroidal Thickness by Enhanced Depth Imaging Optical Coherence Tomography: The Impact of Metabolic Syndrome

Abstract: The choroidal thickness was significantly less in temporal and inferotemporal sectors in patients with MetS than in controls. This may suggest vascular insufficiency around the optic nerve head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Several efforts have been made to overcome the limitations of subfoveal CT measurements in isolation. In some studies, CT measurements at locations other than the macula or subfoveal CT have been attempted in various diseases ( 23 , 79 , 82 , 89 , 104 , 108 ). In others, CT was measured both at the macula and outside the macular region ( 26 , 32 , 77 , 81 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several efforts have been made to overcome the limitations of subfoveal CT measurements in isolation. In some studies, CT measurements at locations other than the macula or subfoveal CT have been attempted in various diseases ( 23 , 79 , 82 , 89 , 104 , 108 ). In others, CT was measured both at the macula and outside the macular region ( 26 , 32 , 77 , 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…Peripapillary CT was lower in type 2 diabetic patients with impaired renal function in a study by Liu et al ( 23 ), and it was positively correlated with the estimated glomerular filtration rate. Loureiro et al ( 89 ) reported that peripapillary CT in the temporal and inferotemporal sectors was significantly lower in patients with metabolic syndrome than in normal controls. Changes in CT not only in the macula but also outside the macula support the hypothesis that choroidopathy occurs in patients with systemic vascular diseases.…”
Section: Choroidal Thickness Measurement Beyond the Maculamentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Optical coherence tomography (OCT) provides a noninvasive, relatively inexpensive, readily available and accurate means of choroid imaging. 9 Choroidal thickness (CT) has been examined across varying cardiovascular risk factors; 10 of note, coronary artery disease, 11,12 heart failure 13 diabetes mellitus without diabetic retinopathy 14 and metabolic syndrome 15 have been associated with reduced subfoveal CT. On the contrary, dyslipidaemia has been suggested to increase CT, 16 while pre-eclampsia might reduce it. 17 Based on the above, we aimed to conduct a metaanalysis on the effect of hypertension on CT values compared with normotensive adults.…”
Section: Therapeutic Advances In Ophthalmologymentioning
confidence: 99%
“…[11] Loureiro et.al found that choroidal thickness (CT) in temporal and inferotemporal sectors were signi cantly lower in MetS patients. [12] Factors pertinent to NAFLD including obesity, [13,14] cardiovascular risk factors [15] and insulin resistance [16] have also proven to be negatively correlated with CT. Even there is robust evidence suggesting lower CT in in ammatory vascular disease such as systemic lupus erythematosus [17] , behçet [18] , scleroderma [19] and so forth [20] .…”
Section: Introductionmentioning
confidence: 99%